Familial amyloid polyneuropathy with chronic paroxysmal dry cough in Mainland China: A Chinese family with a proven heterozygous missense mutation c.349G>T in the transthyretin gene. (February 2019) - Yuan, Zhenhua; Guo, Lina; Liu, Xixi; Xiao, Xuewen; Jiao, Bin; Wang, Junling; Yan, Xinxiang; Tang, Beisha; Shen, Lu
Highlights: This is the first FAP family with a proven missense mutation c.349G>T in Mainland China. This is the first FAP case with chronic paroxysmal dry cough. The heterozygous missense mutation c.349G>T in TTR gene is relatively common in Chinese population. Abstract: Familial amyloid polyneuropathy (FAP) is a rare autosomal dominant disorder characterized by amyloid accumulation in the peripheral nerves and other organs, including the heart, kidney, and eyes. So far, no case with FAP from Mainland China was reported with a heterozygous missense mutation c.349G>T in the Transthyretin ( TTR ) gene. We report a 58-year-old man presenting with progressive peripheral neuropathy, autonomic failure and chronic paroxysmal dry cough. His father, three elder brothers and an elder sister suffered from the similar symptoms. Diagnostic whole-exome sequencing revealed a proven heterozygous missense mutation c.349G>T in exon 4 of the TTR gene, resulting in replacement of alanine with serine at position 117 of the mature protein (Ala117Ser). This is the first FAP family with a proven missense mutation c.349G>T in Mainland China, as well as the first FAP case with chronic paroxysmal dry cough.